Construction of early screening model of lower extremity atherosclerosis in patients with type 2 diabetes mellitus - HOU Xiaowen*, WU Shoutian, LI Mengyuan, MA Xueya, LU Liang, XIE Hui, MA Zuchang (Zhongguo linchuang yanjiu)
Objective To analyze the influencing factors of femoral artery intima-media thickness (IMT) in patients with type 2 diabetes mellitus (T2DM) and to establish a screening model for lower extremity atherosclerosis disease (LEAD) in patients with T2DM. Methods A total of 369 T2DM patients hospitalized in the First Affiliated Hospital of University of Science and Technology of China from July 2022 to February 2024 were retrospectively selected as the research subjects, and they were divided into the IMT thickening group (n =227) and the IMT normal group (n =142) according to whether there was femoral artery IMT thickening. Logistic regression was used to analyze the influencing factors of femoral artery IMT thickening in T2DM patients and to construct a screening model. The receiver operating characteristic (ROC) curve and calibration curve were plotted to evaluate the screening efficacy, calibration degree and discrimination of the model. Results IMT thickening of the femoral artery occurred in 227 (61.5%) patients with T2DM. Elderly age (OR=1.126, 95%CI: 1.089-1.164), high body weight (OR=1.031, 95%CI: 1.005-1.059), long duration of diabetes mellitus (OR=1.049, 95%CI: 1.008-1.091), low HDL-C level (OR=0.321, 95%CI: 0.115-0.896), high cystatin C level (OR=3.032, 95%CI: 1.034-8.889) were the independent risk factors for the occurrence of femoral artery IMT thickening (P＜0.05). The area under the curve of the screening model based on the above indicators was 0.873, with the sensitivity of 0.859, the specificity of 0.711, and the calibration curve was near the ideal curve. Conclusion The screening model has good discrimination and calibration, which can intuitively and easily screen LEAD in T2DM patients and provide a reference for early screening and intervention.